In Vitro Cell Selectivity of Reversible and Irreversible: Electroporation in Cardiac Tissue. (April 2021) - Hunter, David W.; Kostecki, Geran; Fish, Jeffrey M.; Jensen, James A.; Tandri, Harikrishna
Abstract : Background: Pulmonary vein isolation is a common catheter ablation technique used to treat atrial fibrillation originating from the pulmonary veins. However, incomplete lesion formation, pulmonary vein reconnection, and collateral damage to the phrenic nerve and esophagus can occur. Electroporation is a new modality to ablate and has the potential for permanent pulmonary vein isolation and selective efficacy on cardiac tissue; however, strong evidence of selective myocardial injury using electroporation is lacking. Methods: Monolayers of neonatal rat ventricular cardiomyocytes, rat cortical neurons, and esophageal smooth muscle cells were stained with propidium iodide to measure shock-induced cell death. Biphasic shocks (10 ms) were delivered from line electrodes (1 mm separation). Neonatal rat ventricular cardiomyocytes were optically mapped to evaluate postelectroporation electrical conduction. Results: Conduction block occurred when 50% to 80% of the cells near the electrode were killed and required 400±50 V/cm with the electrodes in contact versus 690±70 V/cm with the electrodes 1 mm above the cells ( P <0.01). For 400 V/cm shocks applied in contact with cells, neonatal rat ventricular cardiomyocyte cultures yielded the highest degree of cell death (≈60%) compared with rat cortical neurons (≈40%) and smooth muscle cells (≈20%). When the electrode was raised 1 mm, smooth muscle cells were nearly unaffected by the shock. Conclusions: Cell type alone yielded selective efficacy to electroporation without the confounding influences present in clinical studies, but electrode proximity to the target tissue remains important for efficacy. This exciting result suggests that electroporation may be a more selective modality for pulmonary vein isolation. Graphic Abstract: A graphic abstract is available for this article. Abstract : Supplemental Digital Content is available in the text.